The Profile of Students’ Basic Teaching Skills Through Blended Learning in Microteaching Courses During Covid-19 Pandemic - Istiq'faroh, Nurul (Jurnal Basicedu, 2022)
Due to the COVID-19 pandemic, prospective elementary school teachers must be able to teach both online and offline using a blended learning model. The purpose of this study is to examine the fundamental teaching skills of prospective elementary school teachers in the Microteaching course. This study used qualitative descriptive method. The subjects were students of the Primary School Teacher Education Study Program in University of Nahdlatul Ulama Sidoarjo who programmed Microteaching courses. The data were collected using observations with a performance assessment rubric. Observations were conducted in two stages: first, when students practiced online teaching, secondly, when they practiced offline teaching. The results showed that online teaching skills obtained an average score of 84.71, while offline teaching skills obtained an average score of 85,78. Hence, prospective elementary school teacher students in the blended learning model received an overall score of 85,24, meaning that they were categorized as very good category